Consistency and Stability of Motor Subtype Classifications in Patients With de novo Parkinson’s Disease - Ren, Jingru; Pan, Chenxi; Li, Yuqian; Li, Lanting; Hua, Ping; Xu, Ligang; Zhang, Li; Zhang, Wenbin; Xu, Pingyi; Liu, Weiguo (Frontiers in Neuroscience, 2021)
Objective: Patients with Parkinson’s disease (PD) are commonly classified into subtypes based on motor symptoms. The aims of the present study were to determine the consistency between PD motor subtypes, to assess the stability of PD motor subtypes over time, and to explore the variables influencing PD motor subtype stability. Methods: This study was a part of a longitudinal study of de novo PD patients at a single center. Based on three different motor subtype classification systems proposed by Jankovic, Schiess, and Kang respectively, patients were categorized as TD/indeterminate/PIGD, TDS/mixedS/ARS, and TDK/mixedK/ARK at baseline evaluation and then re-assessed one month later. Demographic and clinical characteristics were recorded at each evaluation. The consistency between subtypes at baseline evaluation was assessed using Cohen’s kappa coefficient (κ). Additional variables were compared between PD subtype groups using the two-sample t-test, Mann-Whitney U test or Chi-squared test. Results: Of 283 newly-diagnosed, untreated PD patients, 79 were followed up at one month. There was fair agreement between the Jankovic, Schiess, and Kang classification systems (κS = 0.383 ± 0.044, κK = 0.360 ± 0.042, κSK =0.368 ± 0.038). Among the three classification systems, the Schiess classification was the most stable and the Jankovic classification was the most unstable. The scores of non-motor questionnaire (NMSQuest) differed significantly between PD patients with stable and unstable subtypes based on the Jankovic classification (p = 0.008), and patients with a consistent subtype had more severe NMSQuest scores than patients with an inconsistent subtype. Conclusion: Fair consistency was observed between the Jankovic, Schiess, and Kang classification systems. For the first time, non-motor symptoms (NMSs) scores were found to influence the stability of the TD/indeterminate/PIGD classification. Our findings support combining NMSs with motor symptoms to increase the effectiveness of PD subtypes.